2016
DOI: 10.3892/ijo.2016.3608
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-195 targets VEGFR2 and has a tumor suppressive role in ACHN cells via PI3K/Akt and Raf/MEK/ERK signaling pathways

Abstract: Abstract. Increasing evidence indicates that dysregulation of miR-195 may contribute to the occurrence and development of multiple types of human malignancies. However, the function and the mechanism of miR-195 in clear cell renal cell carcinoma (ccRCC) are still not fully understood. In the present study, we used qRT-PCR to detect the expression of miR-195 in ccRCC tissues and normal kidney tissues. MTT assay was performed to detect the cell viability of miR-195. Migration and invasion were evaluated by Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…The current study identified that overexpression of miRNA-195 represses the expression level of VEGFR2 in AMC-HN-8 cells. VEGFR2 mediates a variety of important molecular signaling pathways via its downstream signal proteins, including Raf/MEK/ERK1/2, SRC/FAK and apoptosis-related proteins, which serve a key role in regulating tumor development (36). Data from the present study further support the hypothesis that inhibition of VEGFR2/Raf/MEK/ERK and VEGFR2/SRC/FAK pathways regulates cancer cell growth and migration, respectively, mediated by miRNA-195 upregulation in vitro.…”
Section: Discussionsupporting
confidence: 81%
“…The current study identified that overexpression of miRNA-195 represses the expression level of VEGFR2 in AMC-HN-8 cells. VEGFR2 mediates a variety of important molecular signaling pathways via its downstream signal proteins, including Raf/MEK/ERK1/2, SRC/FAK and apoptosis-related proteins, which serve a key role in regulating tumor development (36). Data from the present study further support the hypothesis that inhibition of VEGFR2/Raf/MEK/ERK and VEGFR2/SRC/FAK pathways regulates cancer cell growth and migration, respectively, mediated by miRNA-195 upregulation in vitro.…”
Section: Discussionsupporting
confidence: 81%
“…To a further extent, PI3K/AKT/mTOR is identified as a highly enriched pathway in translocation RCC with TFE3 fusion (TFE3-tRCC) by miRNA microarray analysis [258]. Besides that PIK3R1 regulates EMT and stem-like phenotype of RCC cells through the AKT/GSK3β/CTNNB1 pathway [259], FoxO, PKCε, TPD52, NOTCH1, ETS2, miR-19b, -122, -182, -193a-3p, -195, and -224, as well as LncRNA MALAT1, TP73-AS1 and HOTTIP modulate proliferation, apoptosis, invasion, metastasis, or EMT via PI3K/ AKT pathway [260][261][262][263][264][265][266][267][268][269][270][271][272]. However, only a few of clinical trials of PI3K/AKT inhibitors in touch try to offer hope for KC patients (Tables 2 and 3).…”
Section: Dysregulation Of the Pi3k/akt Pathway In The Genitourinary Smentioning
confidence: 99%
“…Notably, the present study demonstrated that miR-195 suppressed VEGFR2 protein expression in ovarian cancer cells. Sun et al (14) demonstrated that miR-195 suppresses angiogenesis and metastasis of hepatocellular carcinoma through VEGF expression. Wang et al (20) reported that miR-195-5p inhibits tumorigenesis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AKT activation can inhibit ovarian cancer cell apoptosis (11) and is involved in the genesis, development, invasion and metastasis of ovarian cancer (13). Sun et al (14) indicate that miR-195 suppressed cell growth in renal cell…”
Section: Introductionmentioning
confidence: 99%